2019
DOI: 10.1007/s42452-019-1061-8
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and adsorption performance evaluation of activated carbon fibers derived from rayon

Abstract: Activated carbon fiber (ACF) is a material that has attracted significant attention because ACFs derived from several fiber sources have been adapted as filter materials. Here, we described successful ACF preparation via single-and two-step thermal treatments of rayon. Methylene blue adsorption abilities of the resulting ACFs were evaluated. Results indicated that ACFs derived from rayon which is prepared by the two-step thermal treatment demonstrate adsorption ability. Moreover, the average gray-scale intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Image analysis can determine the function of biological materials. Previously, our group evaluated the adsorption capacity of activated carbon fibers in a series of scanning electron microscopy studies (Yoda et al, 2018, 2019), and others used an image processing system (e.g., Calmorph26) for the analysis of the functional morphology of yeast cells (Ohya et al, 2005; Chadani et al, 2021). The results of the present study revealed that machine learning for phase separation classification decreased the amount of time spent; however, the accuracy remains low.…”
Section: Resultsmentioning
confidence: 99%
“…Image analysis can determine the function of biological materials. Previously, our group evaluated the adsorption capacity of activated carbon fibers in a series of scanning electron microscopy studies (Yoda et al, 2018, 2019), and others used an image processing system (e.g., Calmorph26) for the analysis of the functional morphology of yeast cells (Ohya et al, 2005; Chadani et al, 2021). The results of the present study revealed that machine learning for phase separation classification decreased the amount of time spent; however, the accuracy remains low.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon materials are of fundamental importance and developing their applications have broad implications in energy, electronics, and environment (Liu et al 2019;Gopinath et al 2020). Currently, the most commonly used carbon materials include graphene, activated carbons, and carbon bers (Qu et al 2020; Blankenship et al 2017;Zhou et al 2019;Yoda et al 2019). Carbon bers possess the interest aroused in ease of handling and mechanical exibility compared to powdered or granular carbon materials.…”
Section: Introductionmentioning
confidence: 99%